TRANSFORMATION FROM CLASSICAL TEST THEORY (CTT) TO ITEM RESPONSE - VALIDATION, INSTRUMENT; BASSEY, PROFESSOR S. W. (IJRDO -JOURNAL OF MATHEMATICS, 2016)
The paper deals with the transformation from classical test theory (CTT) to item responsetheory (IRT) in research instrument validation. The paper recognizes the contribution ofclassical test theory (CTT) in sustaining the validation of psychological instruments.consequently upon the well – known pitfalls of the CTT and sometimes the misleadinginferences arising from poorly validated and unreliable instrument, the study calls for atransformation from classical test theory (CTT) to item response theory (IRT) or at best anintegration of both. The various methods of validation of IRT were discussed. It wasrecommended that IRT approaches should be vigorously taught to stakeholders and IRTsoftware packages should be made more accessible to intended users.